Competition manipulation in international sport federations` regulations: a legal synopsis - Kuwelker, S.; Diaconu, M.; Kuhn, A. (The International Sports Law Journal, 2022)
Manipulation of competitions has long plagued the sport industry, affecting almost every sport over time. While sharing certain common features, the regulatory provisions and procedural responses to this phenomenon by international federations (IFs), sports` governing bodies, vary on many aspects, including the definition of the specific offence of "competition manipulation" itself, scope of application, especially in relationship to betting, categories of participants, mens rea elements such as recklessness and negligent behaviour, reporting obligations, aggravating and mitigating factors, and applicable sanctions across sports and within a sport/discipline. More nuanced items within internal disciplinary procedure also vary across federations, such as standard of proof and evidence. The purpose of this study is to offer a comparative synopsis of the regulations of 43 IFs governing Olympic and certain non-Olympic sports, to provide a critical overview of specific aspects of the above mentioned factors in the regulations and to identify areas of improvement for the future.